Integral analysis of environmental and economic performance of combined agricultural intensification & bioenergy production in the Orinoquia region. (1st February 2022) - Ramirez-Contreras, Nidia Elizabeth; Fontanilla-Díaz, Carlos A.; Pardo, Lain E.; Delgado, Tulia; Munar-Florez, David; Wicke, Birka; Ruíz-Delgado, Jonathan; van der Hilst, Floor; Garcia-Nuñez, Jesús Alberto; Mosquera-Montoya, Mauricio; Faaij, André P.C.
Abstract: Agricultural intensification is a key strategy to help meet increasing demand for food and bioenergy. It has the potential to reduce direct and indirect land use change (LUC) and associated environmental impacts while contributing to a favorable economic performance of the agriculture sector. We conduct an integral analysis of environmental and economic impacts of LUC from projected agricultural intensification and bioenergy production in the Orinoquia region in 2030. We compare three agricultural intensification scenarios (low, medium, high) and a reference scenario, which assumes a business-as-usual development of agricultural production. The results show that with current inefficient management or with only very little intensification between 26% and 93% of the existing natural vegetation areas will be converted to agricultural land to meet increasing food demand. This results in the loss of biodiversity by 53% and increased water consumption by 111%. In the medium and high scenarios, the intensification allows meeting increased food demand within current agricultural lands and even generating surplus land which can be used to produce bioenergy crops. This results in the reduction of biodiversity loss by 8–13% with medium and high levels of intensification compared to the situation in 2018. Also, a positive economic performance is observed, stemming primarily from intensification of cattle production and additional energy crop production. Despite increasing irrigation efficiency in more intensive production systems, the water demand for perennial crops and cattle production over the dry season increases significantly, thus sustainable management practices that target efficient water use are needed. Agricultural productivity improvements, particularly for cattle production, are crucial for reducing the pressure on natural areas from increasing demand for both food products and bioenergy. This implies targeted investments in the agricultural sector and integrated planning of land use. Our results showed that production intensification in the Orinoquia region is a mechanism that could reduce the pressure on natural land and its associated environmental and economic impacts. Highlights: Inefficient agricultural management transform 93% of current natural vegetation areas. Reducing pressure on natural land could reduce its biodiversity-related impacts. Proper intensification in current arable land generates surplus land for energy crops. Positive economic performance is beheld from cattle intensification and energy crops. Orinoquia region has a potential for sustainable biomass production for energy.